Microstructure and performance of diamond composites fabricated by self-propagating high-temperature synthesis using high-frequency induction as a heat source. (January 2018) - Duan, D.Z.; Xiao, B.; Liu, J.S.; Lai, Z.H.; Xu, W.H.; Zhang, H.T.; Han, L.L.
Abstract: A mixture of Al, Ti, Cu, Ni, and Sn was used as the matrix material to fabricate diamond composites and grinding heads through self-propagating high-temperature synthesis (SHS). High-frequency induction was used as a heat source for preheating to ignite SHS. The SHS was examined, and the microstructure of the reaction products was analyzed by scanning electron microscopy and X-ray diffraction. As a comparison, diamond composites and grinding heads were fabricated by hot pressed sintering (HPS) using Cu-based matrix. The grinding performance of heads was tested in the grinding of Zirconia ceramics. Results showed that ferromagnetic Ni was a key element without which SHS could not start. Increasing frequency prolonged preheating time and decreased combustion temperature. The increasement of Al + Ti content in the matrix aggravated the combustion temperature and thereby aggravated the porosity. The optimal grinding ratios of SHS grinding heads was reached when Al + Ti weight content was 30% and was only 4% lower than that of HPS ones. The grinding forces of SHS grinding heads was lower than that of HPS ones. Carbides Ti3 AlC and Ti3 AlC2 formed on the diamond surface during SHS.